ONLINE STUDENTS’ APPOINTMENT SYSTEM FOR UNIVERSITY ADMINISTRATION - Zurah Abu; Nurul Haswani Jasmisham; Nur Nabilah Abu Mangshor (Journal of Islamic, Social, Economics and Development, 2022)
Current practice in Universiti Teknologi MARA (UiTM) Cawangan Melaka Kampus Jasin is student will go to the administrative unit and set an appointment manually if they want to deal with the administrative personnel. However, there were few issues discovered from a comprehensive online survey that have been conducted among students and administrative staff. 96.49% students who responded, stated that they had an issue that it takes a long time to acquire confirmation of the appointment date. On the other hand, from the perspective of the 4 administrative respondents, they faced the challenge to manually arrange student appointments. Hence, the main aim of this study is to improve the scheduling appointment process from manual practice to online system. The Waterfall Model is applied for in this study, and it is divided into three phases which are requirement analysis, system design, and implementation. An interview session with administrative staffs was conducted to gather information and analyze the requirement needed. The feedback from stakeholders concluded that this online web-based system considers received ‘above average’ level of usability acceptance since the overall mean score of SUS is 68.9. Thus, this study accomplished its aim, and the proposed system can assist administrative staff and students in having a proper and organized appointment process. However, to use this system, it needs further improvements and modifications.